Effects of eye dominance on shade matching and color perception among the dentist population - Pattnaik Kalyani; Kannan Subiksha; Amit Jena; Govind Shashirekha; Saumyakanta Mohanty; Gaurav Sharma (Restorative Dentistry & Endodontics)
ObjectivesThe purpose of this study was to evaluate the influence of eye dominance on color perception, and shade matching.Materials and MethodsA total of 104 participants were selected for the study. There were 3 groups: Group I: 3rd and 4th year dental students and interns (n = 40); Group II: postgraduates (n = 34); Group III: senior residents and faculty members (≥ 6 years of clinical experience) (n = 30). All participants were evaluated for congenital color blindness with Ishihara plates, their dominant eye with Mile's test, and their color perception with the Farnsworth-Munsell 100 hue test. The shade guide test was used for shade matching with a second corresponding set of Vitapan classical shade guides.ResultsThe results of Mile’s test revealed that 60.6% were right-eye dominant and 39.4% were left-eye dominant. There was a statistically significant difference among all participants between the dominant eye and the non-dominant eye in shade matching.ConclusionsThe dominant eye has a positive effect on shade matching and the ability to match shades becomes better with an increase in clinical experience.